Overexpression of α‐synuclein inhibits mitochondrial Ca2+ trafficking between the endoplasmic reticulum and mitochondria through MAMs by altering the GRP75–IP3R interaction. Issue 11 (12th September 2021) - Erustes, Adolfo Garcia; D'Eletto, Manuela; Guarache, Gabriel Cicolin; Ureshino, Rodrigo Portes; Bincoletto, Claudia; da Silva Pereira, Gustavo José; Piacentini, Mauro; Smaili, Soraya Soubhi
Abstract: Mitochondria‐associated ER membranes (MAMs) are formed by close and specific components in the contact sites between the endoplasmic reticulum (ER) and mitochondria, which participate in several cell functions, including lipid metabolism, autophagy, and Ca 2+ signaling. Particularly, the presence of α‐synuclein (α‐syn) in MAMs was previously demonstrated, indicating a physical interaction among some proteins in this region and a potential involvement in cell dysfunctions. MAMs alterations are associated with neurodegenerative diseases such as Parkinson's disease (PD) and contribute to the pathogenesis features. Here, we investigated the effects of α‐syn on MAMs and Ca 2+ transfer from the ER to mitochondria in WT‐ and A30P α‐syn‐overexpressing SH‐SY5Y or HEK293 cells. We observed that α‐syn potentiates the mitochondrial membrane potential (Δψm ) loss induced by rotenone, increases mitophagy and mitochondrial Ca 2+ overload. Additionally, in α‐syn‐overexpressing cells, we found a reduction in ER–mitochondria contact sites through the impairment of the GRP75–IP3R interaction, however, with no alteration in VDAC1–GRP75 interaction. Consequently, after Ca 2+ release from the ER, α‐syn‐overexpressing cells demonstrated a reduction in Ca 2+ buffering by mitochondria, suggesting a deregulation in MAM activity. Taken together, our data highlight the importance of the α‐syn/MAMs/Ca 2+ axis that potentially affects cell functions in PD. Abstract : Overexpression of WT α‐syn and the mutant α‐syn A30P promotes the increase of Ca 2+ levels in mitochondria and the reduction in contact sites between the endoplasmic reticulum and mitochondria, disrupting the IP3R‐GRP75 interaction. Disruption of mitochondria‐associated ER membranes causes a reduction in calcium transfer from endoplasmic reticulum to mitochondria.